BREEDING OF TOMATO (LYCOPERSICON ESCULENTUM) RESISTANT TO TOMATO SPOTTED WILT VIRUS - G. F. Monakhos; T. L. Nguyen; M. L. Nguyen (Овощи России, 2015)
The results of tomato lines resistance test to tomato spotted wilt virus and its comparison to molecular marker SCAR Sw421 genotyping data is shown. A molecular marker SCAR Sw421 analysis allowed identifying homozygous and heterozygous tomato genotypes possessing Sw5 alleles in segregating populations. Selected tomato lines possessing dominant homozygous alleles of Sw5 gene represent a tomato germplasm resistant to tomato spotted wilt virus and would be useful for following crop improvement.